Pelatihan dan Pendampingan Kelompok Tani dalam Mengolah Limbah Pertanian Menjadi Ekoenzim di Kelurahan Bukit Tunggal - Ahmad Saefulloh; Reni Agustiani; Gabriela Elsandika; Julius Telaumbanua; Valentino Tabang; Khairi Khairi; Fitriani Fitriani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This training and mentoring activity for farmer groups in processing agricultural waste into eco-enzymes aims to address the problems faced by farmers in Bukit Tunggal Village. The community service team views this problem as a priority to be solved given the current environmental issues, especially regarding waste management. The method used by the team in implementing the community service activities refers to four important stages to achieve the desired outcomes. The first is preparation. The second is program socialization, focusing on inviting partners to dialogue about the planned activities and providing motivation related to improving the welfare of farmer groups through available resources. The third is Training and Mentoring Farmer Groups in Processing Fruit and Vegetable Waste Produced from the Surroundings into Eco-enzymes. The training is conducted by providing material on eco-enzymes both theoretically and practically. Fourth, evaluation. The results of this training and mentoring activity show that the training was enthusiastically followed by 35 participants from all farmer groups in Bukit Tunggal Village. The activity was considered successful based on the pre-test and post-test conducted by the team. Only 25% of training participants knew about eco-enzymes at the time of the pre-test, but after the training activity, participants' understanding increased to 90% regarding the making of eco-enzymes.